A memoir of the last year of the War for Independence in the Confederate States of America : containing an account of the operations of his commands in the years 1864 and 1865 - Early, Jubal Anderson, 1816-1894. (Columbia : University of South Carolina Press, 2001)
Early was a corps commander in the Army of Northern Virginia.
Campaign in Virginia from the Rapidan to James' River -- Battles of the Wildernes--Operations of Early's Division -- Battles of Spottsylvania Court House--Operations of Hill's Corps -- Hanover Junction--Operations of Early's Division -- Battles of Cold Harbour--Operations of Ewell's Corps -- Campaign in Maryland and the Valley of Virginia -- March to Lynchburg, and Pursuit of Hunter -- March down the Valley, and Operations in the Lower Valley and Maryland -- Battle of Monacacy -- Operations in front of Washington, and Recrossing the Potomac -- Return to the Valley, and Operations There -- Battle of Kernstown -- Expedition into Maryland and Pennsylvania--Burning of Chambersburg -- Retreat to Fisher's Hill, and Subsequent Operations, until the Battle of Winchester -- Battle of Winchester -- Affair at Fisher's Hill -- Retreat up the Valley, and Operations until the Battle of Cedar Creek -- Battle of Cedar Creek or Belle Grove -- Close of the Valley Campaign -- Operations in 1865 -- Letter from General Lee -- Statistics Showing the Relative Strength of the Two Sections during the War.
Originally published: Toronto : Lovell & Gibson, 1866.
Includes bibliographical references (p. xvii-xx).
Keywords: Early, Jubal Anderson, -- 1816-1894.; Generals -- Confederate States of America -- Biography